BANI HAMDAN'S THE LAST ARAB KINGDOM IN THE MEDIEVAL AGE AND THE TOLERANCE TOWARDS RELIGIONS AND SCIENCE ACHIEVEMENT - Meirison Meirison; Sri Chalida; Zerly Nazar (Hadharah: Jurnal Keislaman dan Peradaban, 2022)
Aleppo lived in the era of the Hamdani state, the height of its civilized and cultural era, as its long history did not witness an age full of glories like the era it lived in during the period of Saif al-Dawla al-Hamdani. It became one of the most important scientific and cultural centers in the Islamic world and the meeting place for science, thought, and literature men. I conducted a literature study by collecting literature and verifying and analyzing books and documents, both in published books and manuscripts found on internet sites. I then interpreted and rewritten Bani Hamdan, the last Arab power. In the Middle East. This cultural and civilizational Renaissance had a tremendous impact. And a significant role over many centuries, says the American orientalist Stephen Humphreys about the era of Saif al-Dawla (in his time, Aleppo could match any court in Italy in the Renaissance). Bani Hamdan achieved a lot of progress in various socio-political, economic to scientific development fields. Bani Hamdan's achievements occurred in a crisis filled with political pressure and military and ethnic and religious conflicts. Bani Hamdan is known to be very tolerant of various religions and sects.Keywords: Bani Hamdan's, Tolerance, Science Development